The substitution of barley by other carbohydrates in grass silage based diets to dairy cows - Murphy, M.; Khalili, H.; Huhtanen, P. (Elsevier, 1993)
Four rumen and duodenal cannulated lactating cows were fed grass silage based diets supplemented with either barley (B), or barley and beet molasses (M), or barley and wood molasses (W) or barley and beet pulp (BP) in a 4x4 latin square design. Dry matter consumption was 15 kg day and roughages comprised 57 percent of the diet. Rumen and total digestibilities and milk production were measured and the results correlated with changes in rumen metabolism and microbiology. Fiber digestibility did not differ among diets. Organic matter digestibility for Diet BP in the rumen (64 percent) and total tract (70 percent) was significantly lower than for the other diets. Treatment effects did not influence the flow of amino acids to the duodenum nor the flow of true microbial protein. There were no treatment differences for rumen PH, volatile fatty acid (UFA) concentration or the molar percentages of acetate and propionate. There were lower numbers of cellulolytic bacteria in Diet M compared with the other diets. VFA production rates were highest in diets M and B but at different times after feeding. Treatment differences existed for several of the catabolic enzymes in the rumen. No single parameter of feed composition or rumen status could explain rumen metabolism. Certain enzymes were closely correlated with the rumen digestibility of some feed fractions.